Cross-scale porous structure design leads to optimized thermoelectric performance and high output power for CaMnO3 ceramics and their uni-leg modules. (December 2022) - Chen, Tingting; Wang, Jiyuan; Wang, Xue; Wang, Hongchao; Su, Wenbin; Zhai, Jinze; Mehmood, Fahad; Khan, Mahwish; Wang, Chunlei
Highlights: Three kinds of cross-scale pores with nano-, micro-, and sub-millimeter scales are designed and successfully synthesized for Ca0.96 Dy0.02 Yb0.02 MnO3 ceramics by controlling synthesis process. An ultra-low lattice thermal conductivity κL of 0.39 W/mK comparable to that of the insulating bricks was obtained for the submillimeter-porous ceramics. The pa and ϕ as high as 104.94 mW·cm −2 and 0.54 µW·cm −2 ·K −2 are obtained for nano-porous ceramic module, which are far greater than the performance of the uni-leg CaMnO3 module, and even greater than that of most π-type thermoelectric module composed of CaMnO3 reported up to now. Abstract: In this work, three kinds of cross-scale pores with nano-, micro-, and sub-millimeter scales are designed and successfully synthesized in the same composition of Ca0.96 Dy0.02 Yb0.02 MnO3, and the effects of pore structures with different scales on the performance of thermoelectric materials and uni-leg power generation modules are studied. The average pore sizes (porosities) of these three porous ceramics are about 500 nm (6.0%), 3 μm (28.0%), and 400 μm (68.8%), respectively. It is a notable result, the thermal conductivity downfall sharply with the increasing of pore size and porosity, and an ultra-low lattice thermal conductivity κL of 0.39 W/mK is obtained for submillimeter-porous ceramic owing to multiple phonon scattering and boundary effect of sub-millimeter pores. The achieved lowest value of thermal conductivity can meet the level of insulation bricks. Combining the relative higher power factor, the highest zT of 0.19 is obtained for CaMnO3 thermoelectric sample with micro-scale pores. The highest output power density of pa = 104.94 mW·cm −2 and thermoelectric efficiency factor of ϕ  = 0.54 µW·cm −2 ·K −2 are obtained for thermoelectric module fabricated by nano-porous ceramics, due to the lower contact resistance and enhanced thermoelectric properties of the material, which is far greater than that of most reported CaMnO3 modules. As above finds, the optimal values of κL, zT, pa and ϕ correspond to the three kinds of pores. So trying to exert all advantages of three kinds of pores synergistically in the future further enhances the thermoelectric performance for porous oxide materials and modules simultaneously. Graphical abstract: Image, graphical abstract